Africa 05 - Binder, Lisa (African arts, 2006)
Ten years ago, the artist-led series of events featured exhibitions and programs divided into the visual arts, cinema, music, the performing arts, and literature. Additionally, institutions such as The Camden Arts Centre, Bankside Gallery, Crafts Council, Gasworks, Horniman Museum, and The Photographers Gallery all offered exhibitions and programming that focused on African art and life.